Stem cell-derived exosomes: a potential therapeutic strategy for enhancing tendon stem/progenitor cells function in tendon-bone healing - Junjie Tang; Peng Shen; Xinyuan Wu; Minhao Chen; Hua Xu (Journal of Orthopaedic Surgery and Research)
Abstract Tendon-bone insertion (TBI) injuries and diseases are one of the common musculoskeletal conditions that can severely impair an individual’s daily activities and quality of life. The healing process following an injury is intricate and depending on microenvironmental factors such as mechanical loading, inflammatory responses, and the extracellular matrix. Tendon stem/progenitor cells (TSPCs) primarily contribute to the replenishment of tendon cells via self-renewal and differentiation, which is essential for tendon-bone healing. Exosomes, small extracellular vesicles from various cell types, have attracted significant interest for their potential in regenerative medicine, particularly for treating tendon disorders. Recent studies indicate that exosomes from various cell sources, including mesenchymal stem cells (MSCs) and adipose-derived stem cells (ADSCs), can effectively modulating the activity of TSPCs and enhance their therapeutic potential. This review provides an overview of the mechanisms and functions of stem cell-derived exosomes in altering the properties of TSPCs and facilitating tendon-bone healing. In conclusion, exosomes offer a promising therapeutic approach for TBI injuries. However, further clinical validation is required. Utilizing the regenerative capabilities of exosomes could address promotion of tendon-bone healing and enhance the quality of life for affected patients.